PM2.5-bound PAHs in the indoor and outdoor air of nursery schools in Ha Noi, Viet Nam and health implication - Ha, Vo Thi Le; Hien, Nguyen Thi Thu; Dung, Nghiem Trung; Anh, Nguyen Lan; Vinh, Thai Ha; Yoneda, Minoru (Vietnam Journal of Science and Technology, 2020)
32 daily PM2.5 samples were collected parallelly outdoor and indoor at sixteen nursery schools in Hanoi.15 individual PAHs were analyzed by GC/MS. Mutagenicpotential (MP) and carcinogenic potential (CP) were used to evaluate carcinogenic and mutagenic risk contribution. The mean indoor and outdoor PM2.5 concentrations were 38.7μg/m3 and 93.3 μg/m3 respectively, which exceeded WHO Air quality guideline (2004). The mean ∑15PAH concentrations in indoor and outdoor air samples were 267.1 ng/m3 and 843.4 ng/m3, respectively. There was a good correlation of PM2.5 and PAHs between indoors & outdoors. Indoor MEQå7PAHs was 41.4 ng/m3, whilst outdoor MEQå7PAHs was 137.3 ng/m3. The mean level of indoor TEQå15PAH was 64.6 ng/m3, whereas the outdoor TEQå15PAH was208.8 ng/m3. Dibenz(a,h)anthracene (DahA) and benzo(a)pyrene (BaP) are the most contributors on the carcinogenicity and mutagenity of PAHs indoors and outdoors.